The Effects of Multiple Power Densities of Carbon Dioxide Laser on Photothermal Damage in Rat Skin Tissue - Al-Timimi, Zahra; J Tammemi, Zeina; Akram, Muhammad (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2023)
A CO2 laser produces infrared photons that are largely absorbed by the skin and cause morphological alterations. Twenty-four (Wistar) rats weighing 290-380 g and ranging in age from 8 months to a year were chosen at random and divided into sixteen rats for histological examination and eight rats for tensile testing to determine the extent of injury caused by photothermal damage induced by multiple doses of a CO2 laser. Anesthesia was achieved with intramuscular doses of 10 mg/kg ketamine and 60 mg/kg Xylazine. Two equal 0.5 cm surgical incisions of rat dorsal skin were performed on the left and right sides. One was utilized as a control while the other was subjected to a 10600 nm CO2 laser at various power levels (12.5, 14.1, 15.6, and 17.2) W/cm2. According to the histological analysis, the non-irradiated skin appeared to be flawless, and normal skin layers were observed. The amount of radiation in the irradiated skin samples was closely related to tissue damage. Higher dosages of irradiation resulted in the most severe cellular mutilation. Tissue injury manifested as epidermal obliteration, coagulation, homogeneous hyalinization, and hair loss. The effects of CO2 laser interaction with the skin were explored in-depth in this study. Exposure to the CO2 laser resulted in severe burns and coagulation.